Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/joc.1195
|View full text |Cite
|
Sign up to set email alerts
|

Trends in storminess over the Netherlands, 1962–2002

Abstract: Trends in the annual number of independent wind events over the Netherlands are studied for the period . The events are selected out of 13 hourly 10 m wind speed records that are part of a high quality dataset of near-surface wind observations at Dutch meteorological stations. Comparisons are made with trends in independent wind events selected from geostrophic wind speed records and reanalysis data.The results for moderate wind events (that occur on average 10 times per year) and strong wind events (that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 24 publications
10
91
2
2
Order By: Relevance
“…Any reductions in wind speed could contribute to the observed declines in pan evaporation. There may be two reasons that changes of wind speed have been ignored: (1) The quality of observed records of near-surface wind run is generally too poor for assessing changes in the wind climate (Smits et al 2005). Near-surface wind observations are very sensitive to changes in instrumentation, changes in the exact measuring location or measuring height and changes in local obstacles in the direct surrounds of the measurement site (Smits et al 2005).…”
Section: Wind Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Any reductions in wind speed could contribute to the observed declines in pan evaporation. There may be two reasons that changes of wind speed have been ignored: (1) The quality of observed records of near-surface wind run is generally too poor for assessing changes in the wind climate (Smits et al 2005). Near-surface wind observations are very sensitive to changes in instrumentation, changes in the exact measuring location or measuring height and changes in local obstacles in the direct surrounds of the measurement site (Smits et al 2005).…”
Section: Wind Speedmentioning
confidence: 99%
“…There may be two reasons that changes of wind speed have been ignored: (1) The quality of observed records of near-surface wind run is generally too poor for assessing changes in the wind climate (Smits et al 2005). Near-surface wind observations are very sensitive to changes in instrumentation, changes in the exact measuring location or measuring height and changes in local obstacles in the direct surrounds of the measurement site (Smits et al 2005). (2) Pan evaporation is generally much more sensitive to variations in net irradiance and VPD than to variations in wind speed (Singh and Xu 1997;Roderick and Farquhar 2002).…”
Section: Wind Speedmentioning
confidence: 99%
“…Even though reanalysis datasets are often referred to as 'observations', several studies highlight the possibility of detecting spurious long-term trends in reanalysis data caused, for example, by a regionally changing density of assimilated stations over time. As an example, Smits et al (2005) found no trend in observed storminess over the Netherlands for 1962Netherlands for -2002, in contrast to the trend seen in NCEP/NCAR reanalysis data.…”
Section: Potential Inconsistencies In Long-term Trendsmentioning
confidence: 56%
“…as discussed by the group 'Waves and Storms in the North Atlantic' (WASA 1998;von Storch and Weisse 2008;Lindenberg et al 2012). Also, cyclone detection and tracking algorithms to derive the frequency and intensity of deep lows as a proxy for storminess from historical pressure fields face the problem of lower data density and quality back in time (Smits et al 2005), possibly leading to an apparent increase in high-latitude cyclone activity that is actually due to higher data density (see Sect. 4.3.4).…”
Section: Long-term Wind Climatementioning
confidence: 99%
“…The WASA Group (1998) reported that the storm and wave climate in most of the North Sea has undergone changes on a decadal timescale, probably related to variations in the North Atlantic Oscillation Index with periods of 17, 7.7 and 2.4 years (Loewe and Koslowski 1994). Smits et al (2005) and Weisse et al (2005) report that variations in storminess have occurred during the last 50 years in the southern North Sea. The intensity of the storm and wave climate in the 1990s seems comparable to that observed at the beginning of the 20th century (WASA Group 1998; Dawson et al 2002).…”
Section: Storminess and Sea-level Risementioning
confidence: 99%